Geo-Congress 2019. selected papers from sessions of the Eighth International Conference on Case Histories in Geotechnical Engineering, March 24-27, 2019, Philadelphia, Pennsylvania - Meehan, Christopher L.; Kumar, Sanjeev, 1964-; Pando, Miguel Angel, 1968-; Coe, Joseph T. (American Society of Civil Engineers, 2019)
Selected papers from sessions of the Eighth International Conference on Case Histories in Geotechnical Engineering, held in Philadelphia, Pennsylvania, March 24-27, 2019. Sponsored by the Geo-Institute of ASCE. This Geotechnical Special Publication contains 39 peer-reviewed papers on engineering geology, site characterization, and geophysics. Topics include: characterization and modeling of soils; case studies; sinkholes and karst; seepage, drainage, and permeability; and geophysical engineering. GSP 311 will provide practitioners and researchers a valuable reference on site characterization and engineering geology.
Keywords: Geotechnical engineering -- Congresses.; Geotechnical engineering -- Case studies.; Geotechnical engineering -- Data processing -- Congresses.; Engineering geology -- Case studies.; Engineering geology -- Congresses.; Geophysics -- Case studies.; Geophysics -- Congresses.; elektronické knihy; electronic books